Investigating EFL Students’ Experiences with ReadTheory.org for Reading Comprehension Enhancement: A Narrative Inquiry - Lisawati, Lisawati; Indrasari, Nunun; Misbah, Hasanul (Journal of English Language and Education, 2025)
This study explores the experiences of EFL students at the State Islamic University of Raden Intan Lampung in using the ReadTheory.org website to enhance their reading comprehension. Employing a qualitative narrative inquiry design, the research aims to gain in-depth insights into how students interact with and benefit from the platform. Data were collected primarily through semi-structured interviews and analyzed using thematic analysis. Kolb’s Experiential Learning Theory (1984), which includes four stages—concrete experience, reflective observation, abstract conceptualization, and active experimentation—served as the analytical framework. The findings indicate that ReadTheory.org supports students’ reading development by providing level-adjusted reading texts, which contribute significantly to improving their reading comprehension skills.